Role of abdominal Ultrasonography in diagnosis of acute abdomen - Mekha Ann Andrews; Nirav B Patel; Jatin Jadav; Nilesh J Patel; H L Leuva; R. C. Shah (International Journal of Medical Research and Review, 2015)
Introduction: Ultrasonography has established itself as an invaluable tool in surgery. In surgical practice, abdominal pain is perhaps the most common symptom encountered and almost in every case of abdominal pain surgeon prefers to use the ultrasound to confirm the diagnosis. Although physical examination of the patient is the most important part in proper diagnosis many a time some positive help is required in the form of investigations especially ultrasonography.Methods: This was a study of hundred patients carried out at a tertiary care hospital admitted with complaints of severe abdominal pain except those with a history of trauma or with a history of chronic abdominal pain. Clinical history, physical examination, ultrasonography, per operative findings and histo-pathological examination were used to come to a final conclusion.Result: In this study ultrasonography was diagnostic in 78% of patients. Two patients were misdiagnosed and in 20 patients other investigations were required for the confirmation of diagnosis. The sensitivity and specificity of ultrasound in diagnosing acute appendicitis, renal calculus, liver abscess, mesenteric lymphadenitis, acute pancreatitis and ovarian cyst was 100% and in calculus cholecystitis it was 93.75% and 100% respectively.Conclusion: Ultrasonography is superior in organ system imaging. It helps in showing organ specific lesions and its accurate measurement which is helpful in follow up and response to treatment. Ultrasonography is also helpful in diagnosing alternative disease and to reduce negative laparotomy rate.